Risk factors associated with tuberculosis mortality in adults in six provinces of Argentina - Zerbini, Elsa V. (2017)
Fil: Zerbini, Elsa V. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Respiratorias; Argentina.